(untitled) (Clinics, 2011)
OBJECTIVES: We investigated the influence of sildenafil on cardiac contractility and diastolic relaxation and examined the distribution of phosphodiesterase-5 in the hearts of hypertensive rats that were treated with by NG-nitro-L-arginine methyl ester (L-NAME). METHODS: Male Wistar rats were treated with L-NAME and/or sildenafil for eight weeks. The Langendorff method was used to examine the effects of sildenafil on cardiac contractility and diastolic relaxation. The presence and location of phosphodiesterase-5 and phosphodiesterase-3 were assessed by immunohistochemistry, and cGMP plasma levels were measured by ELISA. RESULTS: In isolated hearts, sildenafil prevented the reduction of diastolic relaxation (dP/dt) that was induced by L-NAME. In addition, phosphodiesterase-5 immunoreactivity was localized in the intercalated discs between the myocardial cells. The staining intensity was reduced by L-NAME, and sildenafil treatment abolished this reduction. Consistent with these results, the plasma levels of cGMP were decreased in the L-NAME-treated rats but not in rats that were treated with L-NAME + sildenafil. CONCLUSION: The sildenafil-induced attenuation of the deleterious hemodynamic and cardiac morphological effects of L-NAME in cardiac myocytes is mediated (at least in part) by the inhibition of phosphodiesterase-5.